Implementation of AHP and Topsis Algorithm on Web-based Application Design to Determine Prospective Winners of Betta Fish Contest - Muhammad Abdurraffi; Fenina Adline Twince Tobing (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
The procurement of beauty competitions from ornamental betta fish has been held throughout Indonesia. The concept of judging and assessment carried out in the ornamental betta fish beauty competition still uses manual bookkeeping. The assessment with the national scale (SNI) is still a concern for the competition participants because of the lack of knowledge about the standard for judging ornamental betta fish contests. DSS (Decision Support System) can be an application development solution to determine the candidate for the winner of the ornamental betta fish contest. The criteria used include color value, neatness value, proportion value, mental value, and appearance value. The calculation method used in conducting this research is AHP and TOPSIS methods. The recommendations made will go through the AHP process for weighting based on the SNI assessment standard, while TOPSIS is used to receive alternatives from users. Then the ranking is based on the preference value generated by the TOPSIS method. This study has obtained the results of the application of the AHP and TOPSIS methods to make a recommendation system for contestants for winning ornamental betta fish correctly. Testing the level of user satisfaction obtains satisfaction results measured through the EUCS (End User Computing Satisfaction) dimension with the help of a Likert Scale calculation, so that it gets a satisfaction value of 87.89%